Micro-raman spectroscopic characterization of a CR-39 detector - Stuani Pereira, Luiz Augusto [UNESP]; Tello Sáenz, Carlos Alberto [UNESP]; Leopoldo Constantino, Carlos José [UNESP]; Campos Curvo, Eduardo Augusto; Coelho Dias, Airton Natanael [UNESP]; Soares, Cleber José; Guedesd, Sandro (SAGE Publications, 2013)
Characterization by micro-Raman spectroscopy of polymeric materials used as nuclear track detectors reveals physico-chemical and morphological information on the material's molecular structure. In this work, the nuclear track detector poly(allyl diglycol carbonate), or Columbia Resin 39 (CR-39), was characterized according to the fluence of alpha particles produced by a 226Ra source and chemical etching time. Therefore, damage of the CR-39 chemical structure due to the alpha-particle interaction with the detector was analyzed at the molecular level. It was observed that the ionization and molecular excitation of the CR-39 after the irradiation process entail cleavage of chemical bonds and formation of latent track. In addition, after the chemical etching, there is also loss of polymer structure, leading to the decrease of the group density C-O-C (∼888 cm-1), CH=CH (∼960 cm -1), C-O (∼1110 cm-1), C-O-C (∼1240 cm -1), C-O (∼1290 cm-1), C-O (∼1741 cm -1), -CH2- (∼2910 cm-1), and the main band -CH2- (∼2950 cm-1). The analyses performed after irradiation and chemical etching led to a better understanding of the CR-39 molecular structure and better comprehension of the process of the formation of the track, which is related to chemical etching kinetics. Copyright © 2013 Society for Applied Spectroscopy.
Keywords: Alpha particle; Chemical etching; CR-39 detector; Micro-Raman spectroscopy; Molecular structure; Allyl diglycol carbonate; CR-39 detectors; Micro Raman Spectroscopy; Molecular excitations; Morphological information; Nuclear track detector; Spectroscopic characterization; Allyl resins; Alpha particles; Chemical bonds; Detectors; Etching; Irradiation; Raman spectroscopy; Chemical analysis